CSDE1 stabilizes AGO2 in embryonic stem cells - Jiang, Yuguan; Waye, Mason; Kakumani, Pavan Kumar (Frontiers in Molecular Biosciences, 2026)
The cold shock domain (CSD)-containing protein, CSDE1, interacts with AGO2 and regulates miRNA function in post-transcriptional gene silencing. While the individual roles of CSDE1 and AGO2 in regulating gene expression underlying stem cell pluripotency and differentiation are well known, the effects of their interaction remain unclear. Here, we demonstrate that CSDE1 stabilizes AGO2 and key pluripotent proteins, NANOG, SOX2, and Oct4, in mouse embryonic stem cells. CSDE1 stabilizes AGO2 and the stem cell markers, preventing their ubiquitination. Further, the N-terminal domain, CSD1, which is necessary for CSDE1 interaction with AGO2, is crucial for maintaining AGO2 levels and the pluripotent proteins, thereby revealing an additional layer of control over AGO2 function and gene expression associated with stem cell fate at the post-translational level.